Near-optimum cost minimisation of transporting bioenergy carriers from source to intermediate distributors - Roberts, Theari (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Industrial Engineering))--University of Stellenbosch, 2010.